Mobile phase effects on the retention on polar columns with special attention to the dual hydrophilic interaction-reversed-phase liquid chromatography mechanism, a review - Jandera, Pavel; Hájek, Tomáš (Journal of separation science, 2018)
Hydrophilic interaction liquid chromatography on polar columns in aqueous-organic mobile phases has become increasingly popular for the separation of many biologically important compounds in chemical, environmental, food, toxicological, and other samples. In spite of many new applications appearing in literature, the retention mechanism is still controversial. This review addresses recent progress in understanding of the retention models in hydrophilic interaction liquid chromatography. The main attention is focused on the role of water, both adsorbed by the column and contained in the bulk mobile phase. Further, the theoretical retention models in the isocratic and gradient elution modes are discussed. The dual hydrophilic interaction liquid chromatography reversed-phase retention mechanism on polar columns is treated in detail, especially with respect to the practical use in one- and two-dimensional liquid chromatography separations.
Keywords: hydrofobní a hydrofilní interakce; statická elektřina; dual retention mechanism; oxid křemičitý; voda; indikátory a reagencie; Static Electricity; chromatografie s reverzní fází; lineární modely; Indicators and Reagents; Chromatography, Reverse-Phase; Ions; Organic Chemicals; gradient elution; Water; ionty; Polymers; Hydrophobic and Hydrophilic Interactions; Linear Models; water adsorption; difuze; Silicon Dioxide; rozpouštědla; Diffusion; chromatografie kapalinová; organické látky; Chromatography, Liquid; Solvents; hydrophilic interaction liquid chromatography; polymery; two-dimensional separation